2004
DOI: 10.1080/13880200490511945
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntiparasitic Activity of Plant Extracts from Panama

Abstract: As a contribution to the search of antiparasitic activity in plants from Panama, a total of 37 extracts obtained from 14 species were assessed against Trypanosoma cruzi (Trypanosomatidae), Trichomonas vaginalis (Trichomonadidae), and Heligmosomoides polygyrus (Heligmosomidae). Also, the cytotoxicity to macrophages was determined, in order to discard, among the active extracts, those cytotoxic to mammalian cells. Tripanocidal activity and cytotoxicity to macrophages were performed by a colorimetric method using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Previous pharmacological studies have revealed that Bixa orellana extracts possess antiprotozoal, anthelmintic and platelet antiaggregant activity (Villar et al, 1997;Barrio et al, 2004). Root extracts have been reported to have spasmolytic activity (Mans et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Previous pharmacological studies have revealed that Bixa orellana extracts possess antiprotozoal, anthelmintic and platelet antiaggregant activity (Villar et al, 1997;Barrio et al, 2004). Root extracts have been reported to have spasmolytic activity (Mans et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Fleischer et al demonstrated the antimicrobial activity of B. orellana leaf and seed extracts against a range of Gram-positive and Gram-negative bacteria and fungi [15]. Moreover, some pharmacological studies have revealed that B. orellana extracts possess an antiprotozoal and anthelmintic effect [16]. Due to their broad antioxidant and antibacterial activities, polar extracts from B. orellana leaves and seeds have been recently proposed as alternative natural preservatives in food matrices [17].…”
mentioning
confidence: 99%
“…orellana L. extracts have antiprotozoal, anthelmintic, platelet antiaggregant, [14,15] and anticlastogenic activity. [16] The root extracts have spasmolytic activity, whereas leaf and branch extracts were effective at neutralizing the effects of snake venoms.…”
Section: Discussionmentioning
confidence: 99%